Masticatory efficiency in complete denture and single implant-retained mandibular overdenture wearers with different occlusion schemes: A randomized clinical trial - Rocha, Cibele O.M. [UNESP]; Longhini, Diogo [UNESP]; Pereira, Rodrigo P. [UNESP]; Lima, Amanda L.O. [UNESP]; Bonafé, Fernanda S.S. [UNESP]; Arioli Filho, João N. [UNESP] (Elsevier, 2021)
Statement of problem: How the masticatory function of complete denture wearers is influenced by the positioning and occlusion of posterior teeth or by the presence of a single mandibular implant is unclear. Purpose: The purpose of this randomized crossover clinical trial was to evaluate the masticatory efficiency of wearers of bimaxillary complete dentures and of wearers of maxillary complete denture and single implant-retained mandibular overdentures, both with bilateral balanced occlusion and lingualized occlusion. Material and methods: Participants received 2 sets of complete dentures with interchangeable teeth in the mandibular prosthesis to allow a change in the occlusion scheme. Subsequently, 1 implant was placed in the mandibular symphysis region, and the mandibular complete dentures were converted to overdentures. The masticatory efficiency was measured by the sieve method for both occlusal schemes. Results: Repeated measures ANOVA showed no statistically significant difference in the masticatory efficiency with the 2 occlusal schemes for conventional complete dentures (P=.707) or overdentures (P=.407). When comparing the type of prosthesis, statistical differences were found for masticatory efficiency (P=.012), with improved mastication for the overdentures. Conclusions: A mandibular single implant improved the masticatory efficiency of patients with complete dentures, but the occlusal scheme did not influence this factor.